KAJIAN PENGGUNAAN CULTIVATOR TIPE MOTOYAMA MTE 70NL UNTUK PENGOLAHAN TANAH DI LAHAN KELOMPOK TANI SYALOM DESA PINASUNGKULAN KECAMATAN MODOINDING - Junita .; Ruland Rantung; Leo Kalesaran (COCOS, 2023)
ABSTRACTThe Cultivator Motoyama MTE 70NL is an agricultural tool and machine provided by theGovernment of South Minahasa Regency for farmer groups in Modoinding District, for thedevelopment of upland projects. This cultivator is used for secondary tillage. Meanwhile, it isnecessary to know the performance of the tools distributed to farmers, so a study is needed tounderstand how the performance of the Motoyama MTE 70NL cultivator is like for tillage bothin conditions without rain and in rainy conditions. Rain conditions are used as a parameter tocompare cultivator performance with conditions without rain. In the treatment of soil conditionsafter rain, the calculation of rainfall is not carried out, even so after the rain is adjusted to the soilconditions, if the soil is too wet, it will be waited until the soil conditions can be processed. Thepurpose of this study was to analyze the performance of the Motoyama MTE 70NL typecultivator for tillage in 2 treatments, namely treatment 1 on soil conditions without rain andtreatment 2 on soil conditions after rain. The area of research land used is 5m x 30m on a flatexpanse. The variables observed in this study include: depth of tillage layer, speed, workingwidth of the tool, travel time, head land, fuel oil, and tool rpm. The results of this study indicatethat tillage using the Motoyama MTE 70NL cultivator in the first treatment resulted in a traveltime of 12.49 minutes, a head land of 49 seconds, fuel oil 213.14 ml, a depth of tillage layer of30 cm. In the two treatments, the travel time was 13.13 minutes, the head land was 50 seconds,the fuel oil was 219 ml, and the depth of the tillage layer was 30 cm. The engine RPM is 2,416.2r/min and the slow rotary gear rpm is 74.4 r/min. In treatment 1 KLT 0.074 ha/hour, KLE 0.071ha/hour, EL 95.94%. In treatment 2 KLT 0.074 ha/hour, KLE 0.069 ha/hour, EL 93.24%.Keywords: Cultivator, Soil Processing